UTAUT Model Analysis on E-Wallet Usage of Vocational School Students - Dzakiyyah, Nuraini; Nugraha, Jaka (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
The purpose of this study is to analyze the acceptance and usage of E-Wallet Dana among vocational students. The research was conducted on 140 students from the 11th and 12th grades of SMKN 1 Lamongan, majoring in Office Management and Business Services (MPLB) and Office Automation and Management (OTKP) programs. The data analysis technique used in this study was Structural Equation Modeling-Generalized Structured Component Analysis (SEM-GSCA) using the GSCA Pro application. The results of this study indicate that Performance Expectancy and Social Influence have a significant positive impact on Behavioral Intention in the acceptance and usage of E-Wallet Dana. However, Effort Expectancy and Facilitating Condition has a non-significant negative impact on Behavioral Intention in the acceptance and usage of E-Wallet Dana. Additionally, Behavioral Intention also has a non-significant negative impact on Use Behavior in the acceptance and usage of E-Wallet Dana. This study provides insights for E-Wallet developers to provide systems that meet the criteria of Performance Expectancy and Social Influence, as these factors significantly influence students' acceptance and usage of the E-Wallet application.